MASIH RELEVANKAH TEORI PORTOFOLIO MODERN? - Erik Alghifari; Bayu Setia; Nugraha Nugraha; Maya Sari (Universitas Lancang Kuning, 2023)
There have been many criticisms of modern portfolio theory. The framework of modern portfolio theory is static, modern portfolio theory assumes that assets are normally distributed. But in times of financial crisis or pandemic, asset class correlations increase, and assets lose value more than normal distributions would expect. This study empirically whether it is possible to apply modern portfolio theory using additional criteria. The criteria proposed are based on financial ratio analysis, using debt ratios expressed as debt to equity and profitability ratios expressed as return on assets. Based on the analysis, modern portfolio theory can be applied using these additional criteria. The analysis shows that portfolios that have a low debt to equity and portfolios with low asset returns or have good performance. But when viewed from the risk, portfolios with a debt to equity ratio of less than one are more diversified so that they are low risk, as well as portfolios with a return on assets of more than 0.1 have a low risk. Risk-averse investors who are trying to experience losses in times of financial turmoil or the current Covid-19 pandemic can add criteria that do not refer to the normal distribution. This research brings new alternative techniques to investors and adds a new dimension to the ongoing relevance of modern portfolio theory.